How to increase productivity : a practical guide to improving the performance of your company's human resources - Modern Business Reports (U.S.A. Alexander Hamilton Institute, 1977)
This report defines productivity and it application to human development. It also show the symptoms of low- productivity organizations and give ways to diagnose and measure the symptoms.
hza 22/02/2019
Loans
Keywords: Production